Speaking up, speaking out: lived experiences of non-tenure track faculty in writing studies - Edwards, Jessica, editor; McGuire, Meg, editor; Sanchez, Rachel, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2021)
Addresses the experiences of those in the non-tenure-track faculty (NTTF) trenches through storytelling and reflection. By connecting NTTF voices from various aspects of writing studies, offers fresh perspectives and meaningful contributions, imagining the possibilities for contingent faculty to be valued and honored in educational systems that often do the opposite.--Provided by publisher.
Practice doesn't always make permanent: directing a writing center as a professor of practice / Rachel Azima -- How student affairs praxis can aid the nexus of emotional labor for NTTF / Peter Brooks -- Contingent faculty in the gig economy: a conversation, comparison, and call / Erica M. Stone and Sarah E. Austin -- "What are you?": rethinking frames for contingent writing center work / Liliana M. Naydan -- Having it all: the costs and opportunities of NTTF's institutional progress / Lacey Wootton -- Ghosts in the building: investigating contingent faculty experiences / Brendan Hawkins and Julie Karaus -- An inconvenient truth: labels and limits in writing center directorship / Megan Boeshart Burelle and Elizabeth J. Vincelette -- A tale of two pities: an inside look at a dual non-tenure track household / Jessica Cory and John McHone -- The sound of silence: negotiating non-tenure track invisibility within the institution / Angie McKinnon Carter, Christopher Lee, and Linda Shelton -- Disunity in a writing community: a post-Ph.D. memoir of professional transitions / Liz Gumm -- Collective bargaining, heterogeneity, and non-tenure track writing faculty / Denise Comer -- Off track and sidetracked / Seth Myers -- Collaboration as antidote to NTTF pressures / Nathalie Joseph and Norah Ashe-McNalley -- Collaboration is critical, but further considerations are needed for NTTF / Heather Jordan -- Faculty community building: portfolio assessment groups as teaching circles / Dauvan Mulally.
Keywords: College teachers -- United States; Writing centers -- United States; Academic writing -- Study and teaching (Higher) -- Social aspects -- United States; Universities and colleges -- United States -- Faculty